2011
DOI: 10.3109/09638288.2011.583308
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation using virtual reality task can improve balance in patients with stroke

Abstract: The telerehabilitation approach in VR supported balance training improved balance in stroke patients and had similar effect on patients' postural functional improvement as conventional balance training in clinical settings. However, when balance training is continued on patient's home instead of the hospital, it would eventually decrease the number of outpatients' visits, reduce related costs and enable treatment of larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 14 publications
2
84
0
5
Order By: Relevance
“…Among these 64 papers were excluded for the following reasons: 35 because the ICTs used were not aimed to rehabilitation purposes ; eight papers were protocols of ongoing studies and results were not available [52][53][54][55][56][57][58][59] ; seven studies did not have a control group [60][61][62][63][64][65][66] ; five because the intervention setting was the same in the two groups 8,[67][68][69][70] ; five were pilot studies [71][72][73][74][75] ; two were secondary analysis of RCTs already included 76,77 ; two studies were excluded because the poor reporting precluded any possible assessment of its eligibility 78,79 . Finally, 12 RCTs for a total of 1047 participants were included in the review ( Figure 1).…”
Section: Studies Selectionmentioning
confidence: 99%
“…Among these 64 papers were excluded for the following reasons: 35 because the ICTs used were not aimed to rehabilitation purposes ; eight papers were protocols of ongoing studies and results were not available [52][53][54][55][56][57][58][59] ; seven studies did not have a control group [60][61][62][63][64][65][66] ; five because the intervention setting was the same in the two groups 8,[67][68][69][70] ; five were pilot studies [71][72][73][74][75] ; two were secondary analysis of RCTs already included 76,77 ; two studies were excluded because the poor reporting precluded any possible assessment of its eligibility 78,79 . Finally, 12 RCTs for a total of 1047 participants were included in the review ( Figure 1).…”
Section: Studies Selectionmentioning
confidence: 99%
“…In regards to balance, VR provides an avenue to implement many of the therapy strategies that have been established for physical and neurological recovery, including repetitive practice, self-observation, biofeedback and imitation of others movements. [35] An extensive evidence base has been established demonstrating the positive effects of utilizing VR for the treatment of balance deficits in neurologically similar patients, including stroke, [81][82][83][84][85][86][87][88][89][90][91][92] Parkinson's disease [80,93,94] and spinal cord injury. [35,36,95,96] Studies of varying levels of complexities in these populations have shown that groups utilizing VR have improved gait speed, standing endurance, and score higher than groups receiving the 'standard of care' on measures of posture, standing and higher level balance.…”
Section: Emerging Techniques For Balance Treatments: Virtual Realitymentioning
confidence: 99%
“…Most of these programs have focused on rehabilitation of physical disability or speech impairment 5,9,13,14,17,18) . In contrast, only a few studies have reported on telerehabilitation for cognition 7,8,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, many telerehabilitation programs have been developed for patients with brain injury 5,9,14,17,18,21) . Most of these programs have focused on rehabilitation of physical disability or speech impairment 5,9,13,14,17,18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation